A litigância climática como um mecanismo para a governança climática: impactos regulatórios das ações baseadas em argumentos de direitos humanos - Oliveira, Letícia Marinho de Andrade (2024)
This work investigates how climate litigation, based on human rights arguments, can act as an effective mechanism in climate governance. The general objective is to analyze the extent in which climate litigation, based on the human right to a healthy environment, contributes to climate governance by holding States accountable and boosting the adoption of more efficient climate policies. Specifically, it seeks to: examine the role of courts in climate governance; analyze the adoption of human rights arguments in climate litigation cases; and evaluate the impacts of structural climate litigation, through practical cases, such as ADPF 708 (Fundo Clima) and Six Youths v. Ministry of Environment and Others. The qualitative and exploratory research uses bibliography accessed on academic platforms, international treaties, IPCC documents and data from the Sabin Center for Climate Change Law and the Climate Litigation Platform in Brazil. It is concluded that climate litigation is indispensable to boost climate governance by increasing countries' ambition, avoiding setbacks and demanding state actions.